Bypassing reproductive barriers in hybrid seeds using chemically induced epimutagenesis. Issue 3 (18th November 2021) - Huc, Jonathan; Dziasek, Katarzyna; Pachamuthu, Kannan; Woh, Tristan; Köhler, Claudia; Borges, Filipe
Abstract: The triploid block, which prevents interploidy hybridizations in flowering plants, is characterized by a failure in endosperm development, arrest in embryogenesis, and seed collapse. Many genetic components of triploid seed lethality have been successfully identified in the model plant Arabidopsis thaliana, most notably the paternally expressed genes (PEGs), which are upregulated in tetraploid endosperm with paternal excess. Previous studies have shown that the paternal epigenome is a key determinant of the triploid block response, as the loss of DNA methylation in diploid pollen suppresses the triploid block almost completely. Here, we demonstrate that triploid seed collapse is bypassed in Arabidopsis plants treated with the DNA methyltransferase inhibitor 5-Azacytidine during seed germination and early growth. We identified strong suppressor lines showing stable transgenerational inheritance of hypomethylation in the CG context, as well as normalized expression of PEGs in triploid seeds. Importantly, differentially methylated loci segregate in the progeny of "epimutagenized" plants, which may allow epialleles involved in the triploid block response to be identified in future studies. Finally, we demonstrate that chemically induced epimutagenesis facilitates hybridization between different Capsella species, thus potentially emerging as a strategy for producing triploids and interspecific hybrids with high agronomic interest. Abstract : Genome-wide loss of DNA methylation induced by 5-Azacytidine allows interploidy and interspecific hybridization barriers to be bypassed in Arabidopsis and Capsella.